Biomimicry in creative contemporary art-making process / Hilal Mazlan - Mazlan, Hilal (Universiti Teknologi MARA, Perak, 2020)
This research was conducted in order to distinguish the different between artist and designer in using biomimicry in creating and constructing their design and artwork. Biomimicry is a method of solving complex problems by looking into Mother Nature. We as human sometimes have our own limits in dealing with things that need to be solved. Nature had provided us with a vast range of knowledge. We just need to look in the right place. By using nature as our mentor, we get to experience the powerful healing effects it has by connecting to the natural world while also finding empowering relief to solve these challenges together. Science and art, the twin engine of creativity in any dynamic culture, are commonly thought of as being as different as day and night. In creating art, artist also shares the same opinion in seeking back inspiration by observing nature.